Nutritional management in the treatment of irritable bowel syndrome (IBS) (Research, Society and Development, 2023)
Western lifestyle and dietary patterns have contributed to the increased incidence of gastrointestinal diseases in the population. The standard Western diet is characterized by ultra-processed foods, which have a pro-inflammatory profile and contribute for the intestinal microbiota imbalance. Of the main gastrointestinal disorders, irritable bowel syndrome (IBS) stands out, a chronic intestinal disorder that already affects a significant portion of the population and whose main symptoms are abdominal pain and discomfort. The main objective of this study is to analyze the main nutritional strategies cited in the literature for treating and managing IBS symptoms, through an integrative literature review. The main articles published in the years 2018 to 2023 were collected and evaluated, and the information gathered in the reading was synthesized in this study. In view of the information collected, the low-FODMAP diet has been shown to be the most effective approach to treating the gastrointestinal symptoms of IBS, reducing the severity of the disease and improving the symptoms of abdominal pain, bloating, and diarrhea in patients. It is emphasized that the diet must be conducted by a specialized nutritionist for proper implementation of the protocol, taking into account the individualities of each patient. IBS is not a syndrome that should be treated in isolation, as it is not triggered by food alone, a multidisciplinary treatment is required.